How different rearing temperatures affect growth and stress status of Siberian sturgeon Acipenser baerii larvae - Aidos, Lucia; Cafiso, Alessandra; Bertotto, Daniela; Bazzocchi, Chiara; Radaelli, Giuseppe; Di Giancamillo, Alessia (Journal of Fish Biology, 2020)
Environmental temperature is one of the critical factors affecting fish development. The aim of this study was to examine the impact of three different rearing temperatures (16, 19 and 22°C) throughout the endogenous feeding phase of the Siberian sturgeon Acipenser baerii. This was performed by assessing (a) larval survival and growth; (b) immunofluorescence localization and expression of genes involved in muscle development and growth - myog and Igf1; and (c) stress status through the expression of thermal stress genes - Hsp70, Hsp90α and Hsp90β - and whole body cortisol. Overall survival rate and larval weight did not differ significantly across temperatures. Larvae subjected to 22°C showed faster absorption of the yolk-sac than larvae subjected to 19 or 16°C. Both at schooling and at the end of the trial, larvae reared at 16°C showed significantly lower levels of cortisol than those reared at 19 or 22°C. IGF-1 immunopositivity was particularly evident in red muscle at schooling stage in all temperatures. The expression of all Hsps as well as the myog and Igf1 genes was statistically higher in larvae reared at 16°C but limited to the schooling stage. Cortisol levels were higher in larvae at 22°C, probably because of the higher metabolism demand rather than a stress response. The observed apparent incongruity between Hsps gene expression and cortisol levels could be due to the lack of a mature system. Further studies are necessary, especially regarding the exogenous feeding phase, in order to better understand if this species is actually sensitive to thermal stress.